Wi-Fi password stealing program using USB rubber ducky - Hansen Edrick Harianto; Dennis Gunawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
A minute is all it takes for a hacker to gain informations from your computer, such as Wi-Fi password. Due to the limited capability of people to remember a lot of complex and unique password, people tend to use the same password for most of their account. This paper aimed to implement Wi-Fi password stealing program in USB Rubber Ducky using USB Rubber Ducky Scripting, Visual Basic Script, Web Server, Command Prompt, and Ducky Toolkit to obtain clear text Wi-Fi password that ever connected to the computer. In the testing phase, the success rate of Wi-Fi password stealing program reached 94.28% with 87.87% obtained personal password is still categorized as guessable password and the password reuse rate reached 81.81%. Thus, Wi-Fi password stealing program can be very dangerous as most of the personal password was used in lots of account and still categorized as guessable.